Developing Listening Skill Through Bottom-Up Strategy - Cut Mailisa Hasriyanti (Research in English and Education Journal, 2017)
This study is intended to find out whether the use of bottom-up strategy improves students’ listening achievement or not. The researcher conducted an experimental research in one of the Junior High Schools in Aceh Besar. One group pretest-posttest design was used in this study. The pre test was given before experimental action in order to know the students’ achievement before the treatment. In addition, to find the differences between the students’ achievement after the treatment, t-score was used. The result shows that the mean score of the pre test is 41.8 and the mean score of the post test is 78.2 and the result of t-score is 10.3. The t-Value at the level significant 0.05 is 2.120 and at the level of significant 0.01 is 2.921 with the degree of freedom 16. The result of this study revealed that the result of t-test is higher than t-Value. In other words, there is a significant difference between the pre test and the post test score. It proves that the use bottom up strategy is effective to improve students’ listening achievement.